Effect of Promotion on The Satisfaction Levels of Teachers in Public Secondary Schools in Kilifi County, Kenya - Kisaka, Joseph (Advances in Social Sciences Research Journal, 2023)
The study set out to investigate the effects of promotion on influencing job satisfaction levels among public secondary school teachers in Kilifi County in the Republic of Kenya. The study was guided by the objectives of determining the effect of gender and promotion on Job satisfaction levels of teachers in public secondary schools in Kilifi County. The study adopted the Descriptive Survey Design to address the statement of the problem and research questions. Information was generated through questionnaires given to teachers within Kilifi County. Using Stratified Sampling technique, 38 schools were selected from public secondary schools in Kilifi County and a semi-structured 5-likert rating scale questionnaire schedule issued to 418 teachers where systematic sampling technique was used. From the sample identified for the study, only 379 were completed and returned. The Questionnaire return rate was 90.6%. During the pilot study, three academic staff members from Pwani University validated the data collection instrument. The instrument had reliability co-efficient of 0.75 found using Pearson’s Product Moment correlation Co-efficient method. The data collected was analysed using Descriptive Statistics such as means, frequencies and percentages provided by Statistical Package for Social Sciences (SPSS), and presented in form of tables, pie charts and Bar graphs. The study found out that gender, as well as promotion of teachers had an effect on their level of job satisfaction. The main recommendations of the study was fair Promotion opportunities if increased may enhance high retention in the profession and improve their job satisfaction of teachers.